Is the incidence of heart attack still decreasing in Australia? Developing reliable methods for monitoring trends in myocardial infarction and coronary heart disease (AUS-MOCHA): a study protocol. Issue 8 (24th August 2016) - Nedkoff, Lee; Knuiman, Matthew; Hobbs, Michael S T; Hung, Joseph; Mathur, Sushma; Beilby, John; Reynolds, Anna; Briffa, Tom G; Lopez, Derrick; Sanfilippo, Frank M
Abstract : Introduction: Accurate monitoring of acute coronary heart disease (CHD) is essential for understanding the effects of primary and secondary prevention and for planning of healthcare services. The ability to reliably monitor acute CHD has been affected by new diagnostic tests for myocardial infarction (MI) and changing clinical classifications and management of CHD. Our study will develop new and reliable methods for monitoring population trends in incidence, outcomes and health service usage for acute CHD and chest pain. Methods and analysis: The study cohort of all CHD will be identified from the Western Australian Data Linkage System using state-wide data sets for emergency department presentation, hospitalisations and mortality data for 2002–2014. This core linked data set will be supplemented with data from hospital medical record reviews, pathology data and hospital pharmacy dispensing databases. The consistency over time of the coding of the different subgroups of CHD/chest pain (ST-elevation MI, non-ST elevation MI, unstable angina, stable angina, other CHD, non-CHD chest pain) in linked data will be assessed using these data sources, and an algorithm developed detailing groups in which temporal trends can be reliably measured. This algorithm will be used for measurement of trends in incidence and outcomes of acute CHD, and to develop further methods for monitoring acute CHD using unlinked and linked data with varying availability of hospitalisation history. Ethics and dissemination: Ethics approval has been obtained from the Human Research Ethics Committees of the WA Department of Health (#2016/23) and The University of Western Australia (RA/4/1/7230). Findings will be disseminated via publication in peer-reviewed journals, and presentation at national and international conferences. There will also be a strong platform for dissemination of new monitoring methods via collaboration with the Australian Institute of Health and Welfare which will assist with promotion of these methods at state and national levels.